Sex-Based Differences in the Drop Vertical Jump as Revealed by Video Motion Capture Analysis Using Artificial Intelligence. Issue 11 (1st November 2021) - Kawaguchi, Kohei; Taketomi, Shuji; Mizutani, Yuri; Uchiyama, Emiko; Ikegami, Yosuke; Tanaka, Sakae; Haga, Nobuhiko; Nakamura, Yoshihiko
Background: Sex-based biomechanical differences during a drop vertical jump (DVJ) may explain the increased risk of anterior cruciate ligament injury in females. Video motion capture using artificial intelligence (VMocap) is a new method for accurate motion analysis. Purpose: To use VMocap to identify sex-based differences in biomechanics during a DVJ in Asian athletes. Study Design: Controlled laboratory study. Methods: A total of 63 female and 61 male Asian soccer players volunteered for this study in 2018. Participants performed a bilateral DVJ using VMocap, and the knee valgus angle (KVA), knee flexion angle (KFA), hip flexion angle (HFA), and lower leg anterior inclination angle (LAIA) were calculated from the motion capture data. These joint angles and inclination angles were evaluated at the time of highest point of the first jump (H1), initial contact (IC), maximum knee flexion (MKF), toe-off (TO), and highest point of the second jump (H2). The unpaired t test was used to compare sex-based differences. Results: At H1, the KVA in females showed more valgus (−2.9° vs −5.4°) and the LAIA in females was greater (29.1° vs 25.7°) versus males ( P < .01 for both). At IC, the KVA in females showed more valgus (−1.3° vs −3.0°) and females had a greater KFA (20.8° vs 14.3°) and LAIA (5.1° vs 0.0°) compared with males ( P < .01 for all). At MKF, female KVA showed more valgus (6.2° vs −9.5°), and females had greater LAIA (36.6° vs 34.6°), smaller KFA (77.5° vs 87.5°), and smaller HFA (55.8° vs 82.0°) compared with males ( P < .01 for all). At TO, female KVA showed more valgus (−0.7° vs −3.1°) and female KFA, HFA, and LAIA were greater (31.7° vs 19.2°; 19.9° vs 16.4°; and 18.2° vs 11.5°, respectively) than males ( P < .01 for all). At H2, females had a greater KFA (18.6° vs 14.6°) and LAIA (13.3° vs 9.9°) than males ( P < .04 for both). Conclusion: Asian female soccer players showed increased KVA and LAIA, decreased KFA and HFA at MKF, and increased KFA at IC and TO compared with their male counterparts in this analysis of the DVJ. Clinical Relevance: Elucidation of kinematic differences between the sexes can aid in predicting injuries.